Lung Cancer Mortality and Radon Concentration in a Chronically Exposed Neighborhood in Chihuahua, Mexico: A Geospatial Analysis - Octavio R. Hinojosa de la Garza; Luz H. Sanín; María Elena Montero Cabrera; Korina Ivette Serrano Ramirez; Enrique Martínez Meyer; Manuel Reyes Cortés (The Scientific World Journal)
This study correlated lung cancer (LC) mortality with statistical data obtained from government public databases. In order to asses a relationship between LC deaths and radon accumulation in dwellings, indoor radon concentrations were measured with passive detectors randomly distributed in Chihuahua City. Kriging (K) and Inverse-Distance Weighting (IDW) spatial interpolations were carried out. Deaths were georeferenced and Moran’s I correlation coefficients were calculated. The mean values (over n=171) of the interpolation of radon concentrations of deceased’s dwellings were 247.8 and 217.1 Bq/m3, for K and IDW, respectively. Through the Moran’s I values obtained, correspondingly equal to 0.56 and 0.61, it was evident that LC mortality was directly associated with locations with high levels of radon, considering a stable population for more than 25 years, suggesting spatial clustering of LC deaths due to indoor radon concentrations.